ESAIC Mellin-Olsen declaration on diversity, equity and inclusion: editorial - Gisselbaek, Mia; Saxena, Sarah; Berger-Estilita, Joana; Ateleanu, Bazil; Brazzi, Luca; Buhre, Wolfgang; Crisan, Iulia; Camilleri-Podesta, Anne-Marie; Coburn, Mark; Durnev, Vesna; Filipescu, Daniela; Ghezel-Ahmadi, David; et al. (European journal of anaesthesiology, 2025)
Export
Gesehen am 02.09.2025